Industrialização, parcelamento do solo e metropolização: o processo de estruturação urbana recente do vetor oeste da RMBH - Sofia Santos Lages (2020)
This research aims to investigate the connection between land subdivision and industrialization in the western vector of the Belo Horizonte Metropolitan Region (RMBH). Formed by the municipalities of Contagem, Betim, Ibirité, Sarzedo, Mário Campos, Igarapé, São Joaquim de Bicas, Juatuba and Mateus Leme, the study area, the axis of the first conurbation of the Belo Horizonte metropolis, has, since the beginning of its occupation, a direct connection with the industrial development of the capital of Minas Gerais. This relationship with industrialization was influenced, above all, by the incentive of the public authorities to strengthen this economic activity, until then supported by the fordist bases of production. In the last decades of the twentieth century, however, the process of industrial production shifted at a global level from the gradual replacement of Fordism by the model known as flexible accumulation, which had repercussions in the reconfiguration of the consolidated industrial plants, as well as in the logistical processes and articulation of production chains. These changes reflected spatially in the RMBH in a pulverization of industries throughout the other municipalities of the region. Since there was no longer the need for concentration on more valued lands adjacent to the industrial centers, these were located in other strategic sites for the articulation of the productive processes. These changes have impacted the demographic indicators of cities close to the areas with greater economic-industrial relevance, which have started attracting a large populational contingent in recent decades, and, consequently, the land subdivision, as a response to the spatial demands emerging from the new economic-productive paradigm. Thus, this study verifies, by crossing demographic, economic, industrial and land subdivision registration data in the western vector of RMBH, between 1998 and 2018, how the recent urban structure of these municipalities is configured, reflecting, among other aspects, the global/national changes that have occurred in the production model. The research, whose method employed is a case study, analyzes data related to the formal models of land subdivision and, in this context, verifies the proposition of new industrial and logistic complexes in the western vector, particularly in the municipalities of Betim and Contagem, as well as the consolidation of areas directly linked to popular and working class housing, in Ibirité and Sarzedo, and others gradually occupied by high standard detached condominiums, as observed in parts of Mário Campos and Igarapé. Analysing the metropolitan structuring on a regional scale, the data point that, in spite of the existent movement of land subdivision in municipalities further from the capital, indicating a linear urban expansion very associated to the main road axes, a strong predominance of formal proposals of parceling persists in those cities nearer Belo Horizonte, whose urban development is in a more advanced stage, reinforcing the centralizing character of the capital alongside the municipalities of Contagem and Betim in the context of the western vector of the RMBH.